2013
DOI: 10.3109/21681805.2013.780185
|View full text |Cite
|
Sign up to set email alerts
|

Increased pulse-wave velocity and carotid intima–media thickness in patients with lower urinary tract symptoms

Abstract: Vascular impairment was found to be associated with LUTS in both men and women. Atherosclerosis-related vascular risk factors are also known to be related to LUTS and both disorders may have pathogenic interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
(56 reference statements)
2
13
0
Order By: Relevance
“…The results demonstrated that altered baPWV, when controlling for confounders, was associated with DO (right side P = 0.01, left side P = 0.03), suggesting that patients with DO are more likely to have atherosclerosis compared to controls. This is consistent with the one human study on patients with OAB, 7 and previous animal studies. [2][3][4][5] Furthermore, Ponholzer et al 19 demonstrated a correlation between vascular risk factors (hypertension, hyperlipidemia, nicotine use, and diabetes mellitus) and the presence of lower urinary tract symptoms (LUTS).…”
Section: Discussionsupporting
confidence: 93%
“…The results demonstrated that altered baPWV, when controlling for confounders, was associated with DO (right side P = 0.01, left side P = 0.03), suggesting that patients with DO are more likely to have atherosclerosis compared to controls. This is consistent with the one human study on patients with OAB, 7 and previous animal studies. [2][3][4][5] Furthermore, Ponholzer et al 19 demonstrated a correlation between vascular risk factors (hypertension, hyperlipidemia, nicotine use, and diabetes mellitus) and the presence of lower urinary tract symptoms (LUTS).…”
Section: Discussionsupporting
confidence: 93%
“…9 Uzun et al carried out a cross-sectional study to investigate carotid artery IMT in patients with LUTS/OAB. 19 AH, diabetes mellitus (DM), and CVD were exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, daytime frequency and nocturia were also significantly higher in men with carotid artery atherosclerosis than in those without it (3.1 ± 1.2 times vs. 1.92 ± 1.12 times). Another study that measured the PWV showed that carotid-femoral PWV was significantly higher in men with LUTS after adjustment for age and glucose level 25 . A study with Japanese patients showed similar findings in that the maximum flow rate in men with atherosclerosis assessed by ultrasound examination of the carotid artery was significantly lower than that in the men without it (13.4 ± 5.5 mL/s vs. 16.7 ± 7.7 mL/s).…”
Section: Discussionmentioning
confidence: 99%